Brief Report: Accuracy of FIB-4 for Cirrhosis in People Living With HIV and Hepatocellular Carcinoma. (15th December 2020) - Torgersen, Jessie; Kallan, Michael J.; Carbonari, Dena M.; Park, Lesley S.; Mehta, Rajni L.; D'Addeo, Kathryn; Tate, Janet P.; Lim, Joseph K.; Goetz, Matthew Bidwell; Rodriguez-Barradas, Maria C.; Bräu, Norbert; Brown, Sheldon T.; et al.
Abstract : Background: Hepatocellular carcinoma (HCC) may develop in the absence of cirrhosis in HIV, and determining how often this occurs can provide insights into mechanisms of carcinogenesis. Studies evaluating the prevalence of cirrhosis in the setting of HCC among people living with HIV (PLWH) often rely on noninvasive markers, such as the Fibrosis-4 Index for Hepatic Fibrosis (FIB-4). However, the accuracy of FIB-4 for cirrhosis in the setting of HCC has not been determined among PLWH. Methods: We conducted a cross-sectional study among PLWH in the Veterans Aging Cohort Study with VA cancer registry-confirmed HCC diagnosed between 1999 and 2015. FIB-4 was calculated using the age, alanine aminotransferase, aspartate aminotransferase, and platelet count obtained closest to, but within 1 year before, HCC diagnosis. Medical records were reviewed within 1 year before HCC diagnosis to determine the cirrhosis status. We evaluated the area under the receiver-operating characteristic curve and performance characteristics of FIB-4 for confirmed cirrhosis. Results: Incident HCC was diagnosed in 302 PLWH. After medical record review, 203 (67.2%, 95% confidence interval: 61.6% to 72.5%) had evidence of cirrhosis. FIB-4 identified patients with cirrhosis with an area under the receiver-operating characteristic curve of 0.67 (95% confidence interval: 0.60 to 0.73). FIB-4 scores >5.0 had a positive predictive value >80% and specificity of >77%, negative predictive value of <41%, and sensitivity of <45%. Conclusion: The accuracy of FIB-4 for cirrhosis in the setting of HIV and HCC is modest and may result in misclassification of cirrhosis in this population. Abstract : Supplemental Digital Content is Available in the Text.